Intervensi Teknik Relaksasi pada Caregiver Cancer yang Mengalami Fatigue - Pradhita Hendriyeni; Allenidekania Allenidekania (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the type of relaxation to prevent fatigue in cancer caregivers. The method used is a systematic review through the Google Scholar database, Pubmed, Sciencedirect and Proquest. The results showed that of the 1,142 articles found in the initial search, 15 articles were selected based on the title and abstract. Articles are read in full and 5 articles are selected according to predetermined criteria. The types of relaxation used in the selected articles are art therapy, yoga therapy, massage therapy and Benson relaxation. In conclusion, Benson relaxation therapy, art therapy, yoga therapy and massage therapy are effective in reducing fatigue levels in cancer caregivers. Keywords : Cancer, Caregiver, Fatigue, Relaxation